2007
DOI: 10.1002/prca.200600541
|View full text |Cite
|
Sign up to set email alerts
|

Altered proteins of the anterior cingulate cortex white matter proteome in schizophrenia

Abstract: Alterations in the circuitry between and within different brain regions including the anterior cingulate cortex (ACC) is implicated in the neuropathology of schizophrenia. The involvement of white matter in schizophrenia is becoming increasingly apparent with reports of structural, morphological and genetic alterations occurring in the disease. The 2-DE was employed to reveal significantly altered proteins within the ACC white matter proteome in a schizophrenia cohort (n = 10) relative to controls (n = 10). Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 49 publications
(22 reference statements)
3
33
0
1
Order By: Relevance
“…Metabolic dysfunction has been found in all psychiatric disorders, consistent with the neuronal plasticity changes observed. Proteomic investigations of schizophrenia post-mortem brain tissue have identified changes in proteins suggestive of disruption of glycolysis in both white (Clark et al, 2007;Sivagnanasundaram et al, 2007) and grey matter (Sivagnanasundaram et al, 2007;Prabakaran et al, 2004), in line with imaging studies showing metabolic hypofunction (Hill et al, 2004;Andreasen et al, 1992). Also, unmedicated bipolar disorder patients in the depressive phase have been found to have reduced prefrontal blood flow and glucose utilization compared to healthy controls (Drevets et al, 1997), and another study demonstrated reduced prefrontal cortex activity of patients in manic phases compared to euthymic patients and controls (Blumberg et al, 1999).…”
Section: The Hypothalamic-pituitary-adrenal Axis Growth Factors and mentioning
confidence: 75%
See 2 more Smart Citations
“…Metabolic dysfunction has been found in all psychiatric disorders, consistent with the neuronal plasticity changes observed. Proteomic investigations of schizophrenia post-mortem brain tissue have identified changes in proteins suggestive of disruption of glycolysis in both white (Clark et al, 2007;Sivagnanasundaram et al, 2007) and grey matter (Sivagnanasundaram et al, 2007;Prabakaran et al, 2004), in line with imaging studies showing metabolic hypofunction (Hill et al, 2004;Andreasen et al, 1992). Also, unmedicated bipolar disorder patients in the depressive phase have been found to have reduced prefrontal blood flow and glucose utilization compared to healthy controls (Drevets et al, 1997), and another study demonstrated reduced prefrontal cortex activity of patients in manic phases compared to euthymic patients and controls (Blumberg et al, 1999).…”
Section: The Hypothalamic-pituitary-adrenal Axis Growth Factors and mentioning
confidence: 75%
“…For instance, reduced levels of glial fibrillary acid glycoprotein (GFAP) have been found in the hippocampus (Muller et al, 2001), prefrontal cortex (Webster et al, 2001;Sun et al, 2009;Si et al, 2004), anterior cingulate cortex (Gittins and Harrison, 2011) and amygdala (Altshuler et al, 2010) of schizophrenia patients, suggestive of changes in astrocytes and synaptic plasticity. Furthermore, alterations of proteins related to the microtubular system, and the micro-and intermediate filaments (Pennington et al, 2008a;Clark et al, 2006Clark et al, , 2007Sivagnanasundaram et al, 2007;Pennington et al, 2008b) have been found, indicative of deficient synaptic pruning and connectivity (Harrison and Weinberger, 2005). Finally, differential expression of the dihydropyrimidinase-related protein 2 (DPYSL2) and neurofilament light chain (NEFL) have been found at the transcript (Hakak et al, 2001;Fallin et al, 2005;Clinton et al, 2003) and proteome levels (Johnston- Wilson et al, 2000;Clark et al, 2007;Sivagnanasundaram et al, 2007;Pennington et al, 2008b;English et al, 2009) in schizophrenia patients Holmans et al, 2009;Ng et al, 2009), as supported by genetic findings.…”
Section: Synaptic Transmission and Structurementioning
confidence: 90%
See 1 more Smart Citation
“…While we found no association between oligodendrocyte density and levels of the myelin-associated protein PLP, we did observe a significant positive correlation between oligodendrocyte density and two cytoskeletal proteins: neurofilament heavy (r = 0.388, p = 0.006) and stathmin (r = 0.306, p = 0.027). Neurofilament heavy is an intermediate filament implicated in the regulation of myelin- Overlap between lists of schizophrenia-associated proteins from 14 previous proteomic studies of cortical grey and white matter [25][26][27][28][29][30][31][32][33][34][35][36][37][38] and top astrocyte-enriched and oligodendrocyte-enriched genes identified by transcriptomic studies [23,24] ated axonal diameter and axonal transport [52], while stathmin modulates the stability of microtubules by inhibiting tubulin polymerization and is present at high levels in oligodendrocyte precursor cells [53].…”
Section: Proteomic Evidence For Oligodendrocyte Alterations In White mentioning
confidence: 98%
“…In order to focus on the most promising candidates, we compiled a list of the top astrocyte-enriched and oligodendrocyte-enriched genes from transcriptomic studies by Cahoy et al [23] and Lein et al [24]. We then compared this with lists of schizophrenia-associated proteins from 14 previous proteomic studies of cortical grey and white matter [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. The intersection of these two datasets is summarized in table 1 and is the main focus of discussion.…”
mentioning
confidence: 99%